2019
DOI: 10.2166/wp.2019.245
|View full text |Cite
|
Sign up to set email alerts
|

Water crises in a water-rich country: case studies from rural watersheds of Nepal's mid-hills

Abstract: The main objective of this paper is to assess the water crisis in Nepal by conducting a series of case studies in rural watersheds in the mid-hills. This was achieved through the applied qualitative method, especially combinations of desk study/structured searches, consultation, and field observation. The ground survey revealed that most of the rural communities in the mid-hills have an unreliable water supply. According to the local stakeholders, 20–25% of water resources have dried up as compared to 20 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 14 publications
1
38
0
Order By: Relevance
“…The mountain water supply was the major source of drinking water source among the hill tribes. This result is similar to a previous study which reported that mountain water was a primary source of freshwater supplied in hilly regions inhabited by the hill tribe people in a mountainous area of Thailand [9,11,21]. Commercial bottled drinking water was also a source of drinking water for the Yao, Karen, Akha, and Lahu people, but not for Hmong and Lisu people.…”
Section: Sources Of Drinking Watersupporting
confidence: 89%
See 2 more Smart Citations
“…The mountain water supply was the major source of drinking water source among the hill tribes. This result is similar to a previous study which reported that mountain water was a primary source of freshwater supplied in hilly regions inhabited by the hill tribe people in a mountainous area of Thailand [9,11,21]. Commercial bottled drinking water was also a source of drinking water for the Yao, Karen, Akha, and Lahu people, but not for Hmong and Lisu people.…”
Section: Sources Of Drinking Watersupporting
confidence: 89%
“…The water was stored in these tanks to allow suspended particles to settle out of the water before further distribution to households using 1 1 2 inch and 1 2 inch PVC pipes. This mountain water supply system is commonly applied in hilly regions [21].…”
Section: Mountain Water Supply Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being one of the richest countries in water resources with more than 2.27% of global fresh water, Nepal is ranked among one of the top countries with a poor drinking water system [24]. Koshi River Basin is one of the three snow-fed watersheds in Nepal and drains around 71,500 km 2 of area in Tibet, Nepal and North Bihar [25].…”
Section: Study Areamentioning
confidence: 99%
“…Nepal's immense water supplies feed directly into the large tributaries of major downstream rivers across South Asia, including the Ganga, thereby providing water to approximately one billion people (Alford and Armstrong, 2010). With close to 2.3% of the world's water resources, Nepal is second only to Brazil when water-wealth (Gurung et al, 2019). However, as abundant as water is in Nepal, close to a fifth of the Nepalese population lacks access to safe drinking water, predominantly due to a lack of infrastructure (UNICEF Nepal, 2018).…”
Section: Nepalese Contextmentioning
confidence: 99%